Um olhar sobre a cidade de João Pessoa - PB (1987 – 2014): uso, percepção e memória das praças do centro histórico da capital - Costa, Marília Jeronimo (2015)
This study of the question: how is it possible to identify public spaces whose design attributes and urban design can establish a real connection between user and place, stimulating perception and memory in relation to these spaces? The overall objective is to understand how public spaces revitalization policies , proposals for the central area of João Pessoa, Paraíba, in the period 1987 - 2014, were able to contribute to the implementation of public spaces (squares) quality, and the revitalization of the downtown area. The specific objective is to analyze the use, perception and memory of users in relation to public spaces of the historic center of João Pessoa, targeted intervention projects aimed at promoting the revitalization, trying to understand the connection between user and place. Was chosen as the object of analysis the squares that are inserted in the first two streets of the original city layout, the New Street and Straight Street, current Av. General Osório and Av. Duque de Caxias, they are: Square Baron of Rio Branco, Venâncio Neiva Square and Square Vidal de Negreiros, considering the historical importance of local and transformations suffered over the decades from 1987 to 2014. A city that was born city without ever being village, endowed with characteristics that made her excel as a uniqueness of small and poor urban center of origin and colonial features, João Pessoa interests us as a research target. The city was not exempted from urban transformations experienced by the main urban centers of the country: it was marked by significant changes that have characterized its development, as the infrastructure, road system and public spaces, witnessing evolution processes such as could be observed like the Rio de Janeiro, Sao Paulo and Recife. The downtown area has undergone over the years a process of devaluation, real estate stagnation and degradation of its environmental conditions. The center is vital to the culture of a city and there is an urgent need to revive the historical center, bringing to light its new capabilities and develop a more humane environment for everyone. The guiding concepts of this research foundation, and also lastrearam the method adopted to conduct the dissertation were presented by Kevin Lynch in his book The Image of the City (1999), articulated yet, the work of Vicente del Rio in Introduction to Urban Design in Planning Process (1990) and Jan Gehl in the book New City Life, for which the journalist specializing in urban planning Natalia Garcia translated and adapted the twelve criteria for determining what constitutes a public space quality. In common, the authors present as a research focus on the study of environmental perception, whose main objectives are to identify the public image and collective memory as instruments to assist the Urban Design in the practice of planning and urbanism. Key - Words: Historical Center, Squares, Public Space and Revitalization.